2017
DOI: 10.12738/estp.2017.3.0017
|View full text |Cite
|
Sign up to set email alerts
|

A New Problem-Posing Approach Based on Problem-Solving Strategy: Analyzing Pre-service Primary School Teachers’ Performance

Abstract: Citation: Kılıç, Ç. (2017). A new problem-posing approach based on problem-solving strategy: Analyzing pre-service primary school teachers' performance. AbstractThis study examined pre-service primary school teachers' performance in posing problems that require knowledge of problem-solving strategies. Quantitative and qualitative methods were combined. The 120 participants were asked to pose a problem that could be solved by using the find-a-pattern a particular problem-solving strategy. After that, task-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(42 reference statements)
0
10
0
9
Order By: Relevance
“…She solved problem as "Hasan works one day and then has three days off before he works again and Ahmet works one day and then has four days off before he works again. According to this Hasan works on 1,4,7,10,13,16,19,22,25,28 March and Ahmet works on 1,5,9,14,19,24,29 March. She found that they work together on 19 March.…”
Section: Results About Making Drawing Strategymentioning
confidence: 91%
“…She solved problem as "Hasan works one day and then has three days off before he works again and Ahmet works one day and then has four days off before he works again. According to this Hasan works on 1,4,7,10,13,16,19,22,25,28 March and Ahmet works on 1,5,9,14,19,24,29 March. She found that they work together on 19 March.…”
Section: Results About Making Drawing Strategymentioning
confidence: 91%
“…Six papers addressed problems out-with the mathematical content that might impact on the problem-posing process, such issues being prevalent for both ITE students and school pupils. For example, lack of understanding of what a word problem is (Kopparla & Capraro, 2018;Ozdemir & Sahal, 2018) the inability to pose contextualised or sensible problems (Ticha & Hospesova, 2013;Kılıç, 2017), grammatical structure difficulties (Ellerton, 2013) and identifying the salient information in posing a problem (English, 1997b). Kopparla and Capraro (2018) conducted an in-depth case study of the problem-posing development of one primary pupil during an intervention.…”
Section: Qualitative Datamentioning
confidence: 99%
“…This requires the students to be able to identify suitable surface-level (or contextual) information in which to embed the mathematical structure. For example, Kılıç (2017) asked participants to pose a word problem that could be solved using the find-a-pattern problem-solving strategy. One participant who could not complete the task reported: 'In fact, I know the pattern-based problem-solving process and how to pose a problem.…”
Section: Qualitative Datamentioning
confidence: 99%
See 2 more Smart Citations